How I, Nicky Flynn, finally get a life (and a dog) : a novel - Corriveau, Art (Amulet Books, 2010)
Nicky Flynn's life gets all turned around when his parents divorce and he is forced to start a new life in a new town and school; but when his mother brings home Reggie, a former seeing-eye dog, from a shelter, Nicky begins to put his life back into perspective.